ANALISIS PENERAPAN UNSUR 5W+1H DALAM MEDIA ONLINE OKEZONE.COM PADA KANAL NEWS PERIODE FEBRUARI 2024 - Fani Nur Jannah (JURNALISTIK DAN MEDIA, 2025)
Mass media functions effectively in disseminating information to a wide audience, encompassing various platforms such as newspapers, magazines, television, radio, and the internet. The advent of new media, particularly the internet, has significantly altered communication paradigms by enabling real-time information access and heightened interactive capabilities. This study aims to investigate the role of mass media in disseminating information and shaping public opinion, specifically analyzing case studies from Okezone.com during February 2024.Using a qualitative descriptive method, data was collected through literature reviews, structured and non-structured interviews, and direct observations on the application of the 5W+1H elements within news articles published by Okezone.com. The findings indicate that mass media play a crucial role in forming public opinions via accurate and balanced reporting. Analysis of news content on Okezone.com revealed that journalists adhered to journalistic standards by incorporating the 5W+1H framework into their reports, thereby producing credible and consumable news for the public.This research recommends continuous improvements in information dissemination quality to solidify its position as primary communication channels in contemporary society. Additionally, adopting digital technologies within the media industry is emphasized to enhance interaction levels and real-time delivery of content. Ultimately, this study contributes to understanding dynamic shifts in mass media dynamics amidst digitization challenges while highlighting essential considerations for effective information dissemination strategies.